Analisis Pengelolahan Air Limbah Domestik (Studi Kasus Gedung A Universitas XYZ) - Arbaningrum, Rizka (Jurnal Proyek Teknik Sipil, 2025)
Sewage treatment plant (STP) functions is to treat household, community and industrial waste has been known for a long time. Most of the STPs are permanently installed , usually the wastewater first flows through the biological treatment stage and then ends at the retreatment stage. XYZ University is one of the universities in South Tangerang. Currently, the STP of XYZ University has not been operating optimally. This research function is to design the STP for tower A Universitas XYZ so that it meets the requirements of the Minister of Environment Regulation No. 68 2016 regarding the quality standards of domestic wastewater. Domestic liquid waste generated by Tower A, XYZ University is 234,576 m3 / day. To manage the waste, an aerobic anaerobic wastewater treatment plant is planned which consists of equalization, pre-settling tanks, anaerobic tanks and aerobic tanks equipped with filter media, and final settling tanks. From the STP management, it is estimated that the quality of domestic wastewater will be BOD5 5,515 mg / l, COD 17,136 mg / l, and TSS 0.648 mg / l.